Effect of the ways of adding stearic acid on properties of sweet potato starch and sweet‐potato‐starch‐based films. (13th October 2015) - Liu, Pengfei; Sun, Shenglin; Lu, Huiling; Hou, Hanxue; Dong, Haizhou
Abstract : Starch‐fatty acid composites were prepared using sweet potato starch (SPS) and stearic acid (SA). The SA was added into the starch system by employing two different ways; i.e ., either prior to heating (Method I) or after heating (Method II). The ways of adding SA changed the SPS pasting characteristics as determined by Rapid Viscosity Analyzer (RVA). In differential scanning calorimetry (DSC) thermograms, both of the composites exhibited a new peak which was regarded as the melting peak of amylose–lipid complex. Scanning electronic microscope (SEM) images indicated that the quantity of intact starch granules decreased (Method I), while the starch granules in the composite prepared by Method II remained the intact morphology. The composite prepared by Method I exhibited lower relative crystallinity than their counterparts. Compared with the control film, the light transmission of the films prepared by Method I showed a decrease of 10.1%, while the films prepared by Method II exhibited a decrease of 5.1%. The films prepared by Method II had better moisture barrier properties than the films prepared by Method I. The films prepared by Method II showed higher tensile strength and elongation at break values compared with the films prepared by Method I.